2016
DOI: 10.4995/muse.2016.3751
|View full text |Cite
|
Sign up to set email alerts
|

Take care of well-being: how facilitators and engagement predict performance of university students

Abstract: The interest in developing a high quality educational system requires constant research of the variables involved in the teaching-learning process. Among these variables, social and academic facilitators are important because there is empirical evidence about their positive relationship with engagement, commitment, selfefficacy, happiness and satisfaction in the academic context. Moreover, the psychological well-being of university students (i.e., engagement) showed to positively affect future academic success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Examples of these are social support, role clarity, developmental opportunities, or autonomy [ 20 , 33 , 45 , 47 ]. However, there are also specific resources that have been studied solely in the university context as academic facilitators (e.g., services, availability of scholarships), choice of courses, or institutions for career preparation [ 48 , 49 ]. Furthermore, in line with hypothesis 3, study resources were negatively associated with student burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of these are social support, role clarity, developmental opportunities, or autonomy [ 20 , 33 , 45 , 47 ]. However, there are also specific resources that have been studied solely in the university context as academic facilitators (e.g., services, availability of scholarships), choice of courses, or institutions for career preparation [ 48 , 49 ]. Furthermore, in line with hypothesis 3, study resources were negatively associated with student burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Both progression towards and attainment of goals may influence well-being (Sheldon and Elliot 1998 ). Previous literature indicated that academic facilitators are positively related to engagement, commitment, satisfaction, and happiness (Martínez et al 2016 ). Similarly, students who made good progress towards their goals at the end of the school term reported enhanced mood compared with the mood at the beginning of the term (Sheldon and Kasser 2016 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Engagement and resilience have also been related (Martínez, Peñalver, & Meneghel, 2016). Given the inherent difficulties and challenges that characterise university life, resilience, defined as the ability to recover and cope with adversity with a more positive perception of problems and difficulties (You, 2016), can be valued as a significant personal strength.…”
Section: Psychological Resources and Their Relationships With Academimentioning
confidence: 99%